Exploring the Symbolism of Nature in the Works of Thomas Hardy: An Eco-critical perspective - Almutairi, Areej Saad (Journal of Humanities & Social Sciences, 2025)
This paper seeks to portray the employment of symbolism as connected with certain manifestations of nature in Thomas Hardy’s novels from an ecocritical perspective. It examines Hardy's symbolic use of natural aspects, including flowers, trees, animals and other elements of the pure Wessex landscape of Hardy’s novels. The significance of this research stems from the fact that Hardy's style and use of nature symbols has been linked to eco-critical studies, which helps the literary genre of eco-criticism find its proper place in contemporary literary criticism. Through exploring Hardy’s naturalistic novels, mainly Tess of the d’Urbervilles (1891), this study tries to sow how symbolism of natural scenery and human behaviour are interwined to create a better understanding of the characters’s psychological and sociological connections.
Keywords: symbolism; eco-criticism; nature; environmentalism; Tess of the d’Urbervilles